The struggle for good care: moral challenges during the COVID-19 lockdown of Dutch elderly care facilities. (10th February 2022) - van der Geugten, Wendy; Jacobs, Gaby; Goossensen, Anne
Abstract : The COVID-19 lockdown of Dutch long-term care facilities between March and May 2020 affected the quality of lives of residents and opposed professional and personal ethics of care. This article, based on 25 in-depth interviews with healthcare chaplains, gives insight into what moral challenges appeared for care professionals. Moral challenges were related to: 'family ruptures', 'residents' loneliness and despair', 'cold-hearted deaths' and 'response and responsibilities'. The findings illuminate the complexity of providing care during the lockdown and show variation in the impact of these ethical experiences, in which both moral distress and moral resilience occurred.